2021
DOI: 10.3390/ijms22062923
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MT1-MMP in Alveolar Epithelial Cells Exacerbates Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a lethal age-related lung disease whose pathogenesis involves an aberrant response of alveolar epithelial cells (AEC). Activated epithelial cells secrete mediators that participate in the activation of fibroblasts and the excessive deposition of extracellular matrix proteins. Previous studies indicate that matrix metalloproteinase 14 (MMP14) is increased in the lung epithelium in patients with IPF, however, the role of this membrane-type matrix metalloproteinase has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…On the contrary, there are MMPs (MMP19 and MMP13) that showed an antifibrotic effect and are downregulated in IPF patients. The role of MMP14 is currently the subject of debate, as several studies have confirmed that it is upregulated in IPF patients [76], whereas a recent publication using a conditional mouse model of lung epithelium-specific MMP14 genetic deletion showed that a lack of MMP14 in lung epithelial cells impaired the spontaneous regeneration of the lung and increased the progression of fibrotic lesions when mice were treated with bleomycin. The absence of MMP14 resulted in increased expression of senescence-associated markers [76,77].…”
Section: The Role Of Ecm In Ipf Onset and Progressionmentioning
confidence: 99%
“…On the contrary, there are MMPs (MMP19 and MMP13) that showed an antifibrotic effect and are downregulated in IPF patients. The role of MMP14 is currently the subject of debate, as several studies have confirmed that it is upregulated in IPF patients [76], whereas a recent publication using a conditional mouse model of lung epithelium-specific MMP14 genetic deletion showed that a lack of MMP14 in lung epithelial cells impaired the spontaneous regeneration of the lung and increased the progression of fibrotic lesions when mice were treated with bleomycin. The absence of MMP14 resulted in increased expression of senescence-associated markers [76,77].…”
Section: The Role Of Ecm In Ipf Onset and Progressionmentioning
confidence: 99%
“…A549 and MRC5 cell lines have been broadly used in IPF studies [ 15 , 69 , 70 , 71 ]. However, the fact that we used A549 and MRC5 cell lines instead of primary cells from IPF patients to explore the collaboration of MUC16 on the fibrotic effects of TGF-β1 could be interpreted as a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered as a proMMP2 activator, expressed on the surface of invasive cancer cells [108]. MMP-14 is overexpressed in AECs of IPF lungs, mainly in hyperplastic cuboidal type 2 pneumocytes and bleomycin-induced lung fibrosis [56,194,195]. It processes types I-III collagen [196].…”
Section: Mmp-13mentioning
confidence: 99%
“…Moreover, bleomycin-induced experimental lung fibrosis is exacerbated by epithelial MMP-14 deficiency since it reveals abnormal proteolytic processing of ECM, a process associated with an epithelial senescence phenotype [55] related to the aggravation of fibrosis [202]. These epithelial senescence cells overexpress TGF-β1 and increase profibrotic markers in fibroblasts such as acta2 and fn1 (Fibronectin) by RT-PCR [56].…”
Section: Mmp-13mentioning
confidence: 99%